2013
DOI: 10.1039/c3sm27886g
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous chain diffusion in unentangled model polymer nanocomposites

Abstract: We studied unentangled poly(ethylene-alt-propylene) (PEP) in a composite with hydrophobic silica particles as a function of the filler concentration. Our neutron spin echo (NSE) experiments cover both the internal dynamics as well as the center of mass diffusion beyond the Rouse time. The key experimental results are (i) all of the chains are equally mobile, (ii) the basic segmental (Rouse) relaxation rate is unaffected even at highest filler concentrations, and (iii) apparently the obstacles reduce significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 51 publications
4
63
1
Order By: Relevance
“…The confined polymer was found to be surprisingly mobile and did not exhibit glassy behavior 29,30 . For unentangled poly(ethylene-alt-propylene) (PEP) there is a strong deceleration of the polymer center of mass motion, but even at the highest silica volume fraction, the segmental chain dynamics is not affected 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The confined polymer was found to be surprisingly mobile and did not exhibit glassy behavior 29,30 . For unentangled poly(ethylene-alt-propylene) (PEP) there is a strong deceleration of the polymer center of mass motion, but even at the highest silica volume fraction, the segmental chain dynamics is not affected 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The tracer diffusivity decreases across a wide range of polymer molecular weight, nanoparticle size 23,24 , and unexpectedly decreases more strongly at higher temperatures 25 . In addition, Richter and co-workers explored the dynamics of entangled 26,27 and unentangled poly(ethylene-altpropylene) (PEP) polymers 28 in nanocomposites by neutron spin echo (NSE) experiments. For entangled polymers it was found that the initial Rouse relaxation rate was unaffected by the hydrophobic silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Because of a finite center of mass diffusion and a low radius of gyration, the interstices between particles were effectively filled and hence a most suitable model system without interphase was obtained. The absence of an interphase was confirmed by neutron scattering and neutron spin echo measurements (38,40). DSC experiments showed a constant glass S138 Ohrt et al transition temperature T g and a decrease in c p at T g with increasing filler concentration as expected from a simple mixing rule (26).…”
Section: Free Volume In Nanocompositesmentioning
confidence: 61%
“…Within a joint effort, we aim to understand the properties of polymers in nanocomposites using a collection of techniques (9,26,27,(37)(38)(39)(40)(41). In the present paper, we focus on poly(ethylene-altpropylene) PEP as soft phase.…”
Section: Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation